La imagen del poeta en la lírica de Carlos López Degregori: una aproximación - Vega Jácome, Selenco (2020)
In the poetry of López Degregori (Lima, 1952), there is the image of a lyric speaker fully aware of his role as a writer: on the one hand, poetry is for him an act of knowledge that allows him to capture the reality in which lives. On the other hand, paradoxically, the practice of this work implies certain limits and risks that prevent him from fully understanding the truths of human existence. This image of poet is quiet well exemplified in "El oficio el deseo el maleficio", one of the most representative texts of Una casa en la sombra(1986).